Age-friendly community an assessment on residential subdivisions of Davao City towards ageing in place - Gomez, Reina Arantxa B. (2020)
This study aimed to age-friendly community development guidelines for subdivisions in Davao City . The study was conducted in order to assess the present condition of residential developments in Davao, specifically with subdivisions, in order to encourage Ageing in Place. A total of six subdivisions located in the sub-urban areas of Davao City, were visited in order to gather information for the study. The information collected was then utilized In order to formulate age-friendly subdivision guidelines. These guidelines centered on the area or domains that are found to be lacking and overlooked in typical residential developments. The spaces identified in the study were also based on the suggestions of the respondents of the study. Other data that was used in the study were the setbacks and other present development guidelines provided in the BPP 244. The study can be replicated for the other housing developments in Davao City since housing development issues and concerns are more or less the same with other residential communities. However, it would be recommended that similar studies be conducted for other residential developments, such as condominiums. It would also be recommended for future similar studies to give more emphasis on the sense of attachment and social connection with ageing in place.